2020
DOI: 10.3390/catal10101133
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Degree of Coverage of the Pt Shell in Pd@Pt Core–Shell Nanocubes for Methanol Oxidation Reaction

Abstract: The synthesis of Pd@Pt core–shell nanocubes was achieved through a direct seed-mediated growth method. This process represents a simple and cost-effective way to produce core–shell nanocubes. The morphology of the Pd@Pt core–shell nanocubes varied from simple cubic to concave cubic, depending on the reducing agent and the Pt content. The selection of the reducing agent is important because the reduction rate is directly related to the shell growth. The catalytic activity and stability of the Pd@Pt core–shell n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Ir-based nanocatalysts have been previously used as OER state-of-the art electrocatalysts in water electrolysis. For comparative purposes, 3.7 nm sized Ir NPs were synthesized using the same procedure as that used for the IrPt NPs except using only the Ir precursor (Figure S5). Then, IrPt, Ir, and commercial RuO 2 NPs were supported onto carbon particles to improve the conductivity, as shown in Figure S6–S10 Figure a,b shows the LSV polarization curves and overpotential at a current density of 10 mA cm –2 for IrPt, Ir, RuO 2 /C, and commercial Pt/C in a range from 1.2 to 1.898 V ( vs RHE), respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ir-based nanocatalysts have been previously used as OER state-of-the art electrocatalysts in water electrolysis. For comparative purposes, 3.7 nm sized Ir NPs were synthesized using the same procedure as that used for the IrPt NPs except using only the Ir precursor (Figure S5). Then, IrPt, Ir, and commercial RuO 2 NPs were supported onto carbon particles to improve the conductivity, as shown in Figure S6–S10 Figure a,b shows the LSV polarization curves and overpotential at a current density of 10 mA cm –2 for IrPt, Ir, RuO 2 /C, and commercial Pt/C in a range from 1.2 to 1.898 V ( vs RHE), respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Then, IrPt, Ir, and commercial RuO 2 NPs were supported onto carbon particles to improve the conductivity, as shown in Figure S6−S10. 30 Figure 4a,b shows the LSV polarization curves and overpotential at a current density of 10 mA cm −2 for IrPt, Ir, RuO 2 / C, and commercial Pt/C in a range from 1.2 to 1.898 V (vs RHE), respectively. According to the OER overpotential, the electrochemical properties of the catalysts followed the order: Ir 66 Pt 34 /C > Ir 25 Pt 75 /C > Ir/C > Pt/C > RuO 2 /C > RuO 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, as the Pt content of the Pd@FePt catalyst increased, the MOR current density did not proportionally increase and showed a maximum at a specific Pt content (Pd@FePt 1/1 ), indicating that the MOR activity improved because of the synergistic effect between the core-shell structure of the Pd@FePt catalyst and the electronic interaction between Fe and Pt. It has been reported that both the Pd@Pt core-shell structure and the FePt alloy can increase MOR activity by appropriately controlling the binding energy of OH or the reaction intermediate of MOR through electronic interactions [14,[22][23][24][25][26][27]. However, it is unclear which of the two effects dominate, but the synergy between the two effects was the greatest at PdFePt 1/1 .…”
Section: Resultsmentioning
confidence: 99%
“…These conditions can enable eco-friendly, low-cost synthetic procedures. We have recently developed a direct seed-mediated growth method for multi-metallic core-shell nanoparticles [11][12][13][14]. Compared with that in a typical seedmediated growth method, the absence of washing and redispersion after seed synthesis can increase the efficiency by reducing the cost and time of nanomaterial production.…”
Section: Introductionmentioning
confidence: 99%